2018
DOI: 10.1177/2192568218769604
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes Associated With Allogeneic Red Blood Cell Transfusions in Spinal Surgery: A Systematic Review

Abstract: Study Design: Systematic review. Objectives: The objectives of this systematic review were to report the available clinical evidence on patient outcomes associated with perioperative allogeneic red blood cell (RBC) transfusions in adult patients undergoing spinal surgery and to determine whether there is any evidence to support an association between transfusion timing and clinical outcomes. Methods: A systematic review of the PubMed, EMBASE,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…The present study identified PRC preparation factors that predicted the risk of PRC transfusions in developing countries. The prevalence of PRC transfusion (43%) during the study period at this spine referral center hospital was similar to some studies (40%-81%) 2,13,15 but in contrast with other previous studies (5%-32%) 9,12,14 .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The present study identified PRC preparation factors that predicted the risk of PRC transfusions in developing countries. The prevalence of PRC transfusion (43%) during the study period at this spine referral center hospital was similar to some studies (40%-81%) 2,13,15 but in contrast with other previous studies (5%-32%) 9,12,14 .…”
Section: Discussionsupporting
confidence: 88%
“…This study has limitations: (1) The prediction model must be validated in a more extensive prospective study before use. (2) The study retrospectively analyzed the collected data; some data did not include all types of posterior spinal fusion (small number of PLIF (12 cases) due to this type of fusion more risk of nerve root injury than TLIF), patient bleeding disorder, experience of an orthopedist, and preoperative blood predictors (active partial thromboplastin time (APTT), prothrombin time (PT), and other clotting factors were not routine preoperative laboratory). (3) The model was also based on a single center, which requires external validation for good predictive performance, particularly in other public health hospitals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Excessive bleeding can be associated with complications and increased hospital LOS. [22][23][24] There are different methods to estimated blood loss, 25 we decided to use difference between preoperative and postoperative hemoglobin as a more reliable parameter according to Purvis et al 26 Low levels of hemoglobin are related to delayed wound healing, especially when combined with risk factors such as low oxygenation, higher age, diabetes, obesity, alcoholism, smoking, and poor nutrition status. Those are important factors to determine patient's frailty index.…”
Section: Discussionmentioning
confidence: 99%
“…Repine [ 27 ] and Spinella [ 8 , 17 ] demonstrated distinct advantages of FWB transfer in military trauma, including significantly better 24-h and 30-day survival. Blackburn [ 32 ] also demonstrated a significant dose–response relationship between postoperative, morbid events like infections and prolonged hospital stay and CT.…”
Section: Discussionmentioning
confidence: 99%